Bibliometric Analysis: The Use of Technology in Arabic Language Education - Lili Musyafa'ah; Farah Nur Jihan; Sarah Hajar Aini; Ghina Ramadani (Journal of Practice Learning and Educational Development, 2025)
The study aims to analyze publication trends related to the use of technology in Arabic language education from 2008 to 2024. In today's fast-growing digital age, information and communication technology (ICT) has become an integral component in many aspects of life, including in the field of education. The integration of ICT in Arabic language education offers great potential for improving the effectiveness of teaching and learning methods. The method used in this research is bibliometric analysis, which allows researchers to evaluate and mapp publication patterns in this field in depth. Data was collected through searches of documents with the keyword "arabic language education technology" in various academic databases, including journal articles, books, and conference proceedings, which resulted in a total of 23 relevant documents. The analysis is done using the Mendeley Desktop and VOSviewer applications to visualize and analyze the situation and identify the dominant themes in the publication. Research results show that the use of ICT in Arabic language education has had a significant impact on the teaching methods used. Technology has increased the flexibility and accessibility of learning materials, as well as creating a more interactive and attractive learning environment for students. The study also highlights the importance of Arabic proficiency among non-Arabic speakers, especially in countries with a large Muslim population, and emphasizes the need to develop innovative teaching methods.Furthermore, the findings highlight the urgent need for better training for educators to make optimal use of technology. This research provides valuable insights for educators, policymakers, and technology developers in their efforts to improve the quality of Arabic language teaching in the future. By understanding trends and developments in the use of technology, stakeholders can design and implement learning strategies that are more effective and responsive to student needs.